'I finally understand my mistakes' - the benefits of screencast feedback - Bjerknes, Anne-Line; Opdal, Lars; Canrinus, Esther T. (Technology, pedagogy and education, 2024)
This study explores the impact of screencast feedback on maths tests for junior and high school students. While prior research emphasises the influence of feedback on learning, its effectiveness varies with type and delivery. Although studies in higher education observe improved precision and emotional connections through screencast feedback, its applicability in secondary education remains understudied. The authors surveyed 99 students, collecting responses via an 11-item questionnaire after the students had received feedback. Through thematic analysis, they found 72% favoured video feedback due to its clarity, depth and personal touch. Conversely, 17% preferred written feedback for efficiency. These findings underscore the benefits of screencasting feedback, highlighting its comprehensibility and individualised nature. Given the rise of digital learning, educators are encouraged to adopt screencasting as a valuable tool for enhancing feedback in academic settings.